2008
DOI: 10.1029/2007jc004533
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the early development of harmful algal blooms on the West Florida Shelf with the aid of Lagrangian coherent structures

Abstract: [1] Several theories have been proposed to explain the development of harmful algal blooms (HABs) produced by the toxic dinoflagellate Karenia brevis on the West Florida Shelf. However, because the early stages of HAB development are usually not detected, these theories have been so far very difficult to verify. In this paper we employ simulated Lagrangian coherent structures (LCSs) to trace potential early locations of the development of a HAB in late 2004 before it was transported to a region where it could … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…The coefficient values for the Philippine region are difficult to constrain, so we used typical values (e.g., Olascoaga et al 2008). They include the maximum rate of nutrient-limited phytoplankton growth m 5 0.4 day 21 , the half-saturation constant N 0 5 0.5 (mmol N m 23 ), the portion of recyclable nutrients in dead phytoplankton 5 0.1, and the linear phytoplankton loss s 5 0.1 day 21 .…”
Section: Biological Modelmentioning
confidence: 99%
“…The coefficient values for the Philippine region are difficult to constrain, so we used typical values (e.g., Olascoaga et al 2008). They include the maximum rate of nutrient-limited phytoplankton growth m 5 0.4 day 21 , the half-saturation constant N 0 5 0.5 (mmol N m 23 ), the portion of recyclable nutrients in dead phytoplankton 5 0.1, and the linear phytoplankton loss s 5 0.1 day 21 .…”
Section: Biological Modelmentioning
confidence: 99%
“…The productivity and biodiversity of these ecosystems relies on the photosynthetic activity of many benthic organisms that utilize available sunlight that passes through the water column [4]. The Inputs of organic matter from land are usually loaded with nutrients, promoting the development of algal blooms with particular optical signatures detectable from space [41][42][43]. Water masses carrying organic matter have been tracked moving south from the west coast of Florida to the Dry Tortugas National Park [41], and consequently contributing to the development of higher phytoplankton densities, including harmful algae species.…”
Section: Introductionmentioning
confidence: 99%
“…It is precisely this void that has provided the stimulation for recent work relating to LCSs (Haller 2000;Haller and Yuan 2000;Haller 2001a,b;Haller 2002;Shadden et al 2005). This type of analysis has proven to be extremely useful in applications Olascoaga et al 2006;Mathur et al 2007;Koshel and Prants 2006;Coulliette et al 2007;Yuan et al 2004;Rogerson et al 1999;Beron-Vera et al 2008;Olascoaga et al 2008) but it relies heavily on numerical calculations and has its own limitations (Shadden et al 2005). In this study we have shown that, despite some shortcomings associated with both KAM theory and LCSs, both sets of ideas provide critically important insight into the problem we have studied-transport in a three-gyre system.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For reasons that will be discussed below, numerically computed stable and unstable manifolds are usually referred to as Lagrangian coherent structures (LCSs) (Haller 2000;Haller and Yuan 2000;Haller 2001a,b;Haller 2002;Shadden et al 2005). These ideas have been previously explored and applied to oceanographic transport problems (Coulliette and Wiggins 2001;Wiggins 2005;Lekien et al 2005;Olascoaga et al 2006;Poje and Haller 1999;Koshel and Prants 2006;Coulliette et al 2007;Rogerson et al 1999;Yuan et al 2004;Samelson and Wiggins 2006;Samelson 1992;Mancho et al 2008;Beron-Vera et al 2008;Olascoaga et al 2008). Transport in a double-gyre system has previously been studied in Coulliette and Wiggins (2001) and Poje and Haller (1999).…”
Section: Introductionmentioning
confidence: 99%